Monitoring financial flows for health research : behind the global numbers - Landriault, Erik; Matlin, Stephen A; Global Forum for Health Research (Geneva : Global Forum for Health Research, 2009)
This study aims to provide NGOs and decision-makers with an overview of currently available information on resource flows into health research. It paints the picture of a changing landscape, with an increased number of actors and increases in resources for health promotion and health research in developing countries. The document provides statistical data on global spending on R&D for health, looks at trends and patterns of morbidity and mortality and discusses health research challenges and priorities for the public sector.
Keywords: Health Services Research; Research; Public Health Systems Research; Investments; Developing Countries